Contribution to the immunodiagnosis of human leptospirosis: emphasis to monoclonal antibodies - M. A., Ribeiro, (2004)
The best serological test for leptospirosis laboratorydiagnosis remains the microscopic agglutination test (MAT).Because of the complexity of MAT, we have been developedsome rapid screening tests for leptospiral antibodies detectionin the acute phase of infection. In the decade of 80, a passivehemagglutination test employing polysaccharide fractions ofleptospires was considered appropriate for early diagnosis,but its antigen preparation included “common antigens”recognized by antibodies from 4% of healthy individuals. Anew ELISA (enzyme-linked immunosorbent assay) employing proteinase K resistant immunodominant antigens wasdeveloped and its potential diagnosis evaluated. Thistechnique, the PK-ELISA, presented 89.9% sensitivity and97.4% specificity, and satisfied the requeriments needed forserological screening tests of human leptospirosis. However,some of the reagents used in its antigen preparation areimported and very unstable. So, it was proposed, in a“Cooperative Research Accordance” between Instituto AdolfoLutz and Laboratório Fleury, to try new approaches withmonoclonal antibodies. Two hibridomas secreting specific monoclonal antibodies (MAb) were selected: one, against anepitope detected in 16 of 23 members of the genus Leptospira(clone A12P4) and the other, specific to the icterohaemorragiaeserogroup (clone H7P1). The MAb A12P4, a G2 (IgG2B)immunoglobulin, reacted with an epitope present in the 16-18kDa components of icterohaemorragiae serogroup and withthe 75-84 kDa components of serovars copenhageni andcanicola, after whole-cell lysates of the leptospires wereseparated by sodium dodecyl sulfate- polyacrylamide gelelectrophoresis. The MAb H7P1, which is an IgG, reacted withan epitope common to several fractions of molecular weightabove 21 kDa of strain RGA and with the 21-22 kDa and the 75-82 kDa components of strain M-20. Both monoclonal antibodieswere employed in enzyme immunoassays for detecting specificantibodies in serum samples serially colleted from 52 patientswith leptospirosis, and from the control group, which consistedof sera from 57 patients with other diseases included in the tests, however, were not satisfactory. A new ELISA wasdeveloped in the present study employing an antigensuspension “AgMc”, purified by affinity chromatography withCNBr-activated Sepharose 4B coupled to the monoclonalantibodies described above. The results obtained with thistest were compared to the MAT and to the classical IgM ELISA(ELISA c). The new method, “AgMc ELISA”, presentedserological indices, relatively to reference test MAT, of 80.70% and 83.33 % of sensitivity and specificity, respectively;positive and negative predictive values of 69.70 % and 90.10%, respectively, and general agreement index of 82.49 %. So,this test was not considered a promising approach to rapiddiagnosis of human leptospirosis. Moreover, the proportionof patients diagnosed as having leptospirosis by the “AgMcELISA” and the MAT differ significantly. The possibleexplanations for the results obtained are discussed.